Cover Picture: Energy and Chemicals from the Selective Electrooxidation of Renewable Diols by Organometallic Fuel Cells (ChemSusChem 9/2014). Issue 9 (19th August 2014) - Bellini, Marco; Bevilacqua, Manuela; Filippi, Jonathan; Lavacchi, Alessandro; Marchionni, Andrea; Miller, Hamish A.; Oberhauser, Werner; Vizza, Francesco; Annen, Samuel P.; Grützmacher, H.
<x xml:space="preserve">Abstract</x> The Front Cover image is an allegorical representation of the organometallic fuel cell (OMFC) system described in the paper of F. Vizza, H. Grützmacher et al. The dance of the three graces is the fulcrum: they dance together forming a circle representing the three organometallic complexes of the catalytic cycle for the selective electro‐oxidation of diols obtained from renewable resources to the corresponding carboxylate compounds. Simultaneously, the electrons (Eros) move towards the cathode electrode (Flora and Zephyr), where oxygen is reduced to OH− producing energy. More details can be found in the Communication on page 2432 (DOI: 10.1002/cssc.201402316), while more information about the research group is available in the Cover Profile (DOI: 10.1002/cssc.201402750).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>